How to manage barangay finances - Ursal, Sofronio B. (Quezon City Good Governance Books, 2001)
A guide in the proper management and prudent utilization of barangay resources for all local government officials concerned with barangay finances.
Purpose: May be used as a "guide by the barangay officials in the performance of their functions," and in management of barangay finances.
Barangay finance -- Barangay governments -- Sangguniang barangay -- Barangay (functions and branches) -- Budget preparation and authorization -- Accountability -- Katipunan ng Kabataan.
Keywords: Local finance -- Management. -- Philippines; Finance, Public -- Philippines -- Handbooks, manuals, etc